2008
DOI: 10.1002/dvdy.21644
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine enhances cardiac neural crest cell attachment in vitro by increasing intracellular calcium levels

Abstract: Elevated homocysteine (Hcys) increases the risk of neurocristopathies. Previous studies show Hcys inhibits neural crest (NC) cell migration in vivo. However, the mechanisms responsible for this effect are unknown. Here, we evaluated the effect of Hcys on NC cell attachment in vitro and determined if any of the effects were due to altered Ca 2؉ signaling. We found Hcys enhanced NC cell attachment in a dose and substratedependent manner. Ionomycin mimicked the effect of Hcys while BAPTA-AM and 2-APB blocked the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…The CHD that result from exposure to elevated homocysteine, especially those effecting the outflow tract, are likely to be related to the impact that homocysteine has upon the development of the cardiac neural crest, (Brauer and Rosenquist, 2002;Boot et al, 2003Boot et al, , 2004Boot et al, , 2006Tierney et al, 2004;Rosenquist et al, 2007;Heidenreich et al, 2008). A number of biological, chemical, and genetic mechanisms have been postulated for the teratogenic effect of homocysteine during heart development, some of which have been reviewed previously van Mil et al, 2010).…”
Section: Indirect Effects Of Insufficent Folate Upon the Cardiac Neurmentioning
confidence: 99%
“…The CHD that result from exposure to elevated homocysteine, especially those effecting the outflow tract, are likely to be related to the impact that homocysteine has upon the development of the cardiac neural crest, (Brauer and Rosenquist, 2002;Boot et al, 2003Boot et al, , 2004Boot et al, , 2006Tierney et al, 2004;Rosenquist et al, 2007;Heidenreich et al, 2008). A number of biological, chemical, and genetic mechanisms have been postulated for the teratogenic effect of homocysteine during heart development, some of which have been reviewed previously van Mil et al, 2010).…”
Section: Indirect Effects Of Insufficent Folate Upon the Cardiac Neurmentioning
confidence: 99%
“…Alternatively, it has been hypothesized that the increase in homocysteine that accompanies folate insufficiency is the actual risk factor. We [12-14] and others [15,16] have shown that hyperhomocysteinemia is associated with conotruncal defects in the chicken embryo model, while recent evidence indicates that maternal hyperhomocysteinemia also may be associated with conotruncal defects in humans [17]. In fact it appears that hyperhomocysteinemia, rather than hypomethylation, is a more important risk factor in the development of heart defects [18].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that early emerging trunk NC cells reach the DA in discrete migratory streams through the rostral somite halves, under the guidance of CXCR4/CXCL12 signaling (Kasemeier-Kulesa et al, 2010). We were surprised to find only random calcium transients during NC cell migration in the head and trunk, since previous in vitro studies have identified calcium activities in fibroblasts (Wei et al, 2010), NC cell delamination (Newgreen and Gooday, 1985) and attachment to the substrate (Heidenreich et al, 2008), and motor axon guidance (Hanson and Landmesser, 2004). In contrast, the pattern of calcium transients after NC cells reached the DA was exciting (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…Typical calcium indicators, such as Fluo-4 AM (Heidenreich et al, 2008) require invasive delivery into embryos or can be soaked into cells and tissue in vitro by external application. This severely limits the ability to accurately deliver calcium indicators to discrete cell subpopulations within the developing embryo during precise times of complex morphogenetic events.…”
Section: Introductionmentioning
confidence: 99%